2021
DOI: 10.1021/acs.est.0c07621
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the NO/NO2 Ratio on Oxidation Product Distributions under High-NO Conditions

Abstract: Organic oxidation reactions in the atmosphere can be challenging to parse due to the large number of branching points within each molecule's reaction mechanism. This complexity can complicate the attribution of observed effects to a particular chemical pathway. In this study, we simplify the chemistry of atmospherically relevant systems, and particularly the role of NO x , by generating individual alkoxy radicals via alkyl nitrite photolysis (to limit the number of accessible reaction pathways) and measuring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…As the photochemical reactions proceed, the NO/NO 2 ratio rapidly decreased to the typical ratio of ∼0.1, which was similar to the daytime atmosphere level. 88,89 Furthermore, the HO 2 concentrations we simulated by the Master Chemical Mechanism (MCM) were at the atmospheric level (∼10 8 molecules cm −3 ). 90 We put 4 min-average time-dependent data of parallel experiments of the same reaction system together and ran a two-product model 91 (Text S9); the SOA yields of the three nalkylcyclohexanes as a function of SOA mass concentrations are illustrated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…As the photochemical reactions proceed, the NO/NO 2 ratio rapidly decreased to the typical ratio of ∼0.1, which was similar to the daytime atmosphere level. 88,89 Furthermore, the HO 2 concentrations we simulated by the Master Chemical Mechanism (MCM) were at the atmospheric level (∼10 8 molecules cm −3 ). 90 We put 4 min-average time-dependent data of parallel experiments of the same reaction system together and ran a two-product model 91 (Text S9); the SOA yields of the three nalkylcyclohexanes as a function of SOA mass concentrations are illustrated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory studies revealed that the [NO]/[NO 2 ] ratio can effectively govern SOA formation in high-NO x experiments. 108,109 Chen et al found that [NO]/[NO 2 ] ratios have a negative relationship with SOA yield from the high-NO x photooxidation of methacrolein and α,β-unsaturated aldehydes. 108 More recently, Nihill et al produced individual RO directly via alkyl nitrite photolysis to rule out the effects of NO x on initiating the oxidation chemistry of SOA precursors.…”
Section: Factors Affecting Aromatic Soa Formationmentioning
confidence: 99%
“…RO is converted to RO 2 , which can involve a variety of reactions. 109 In high-NO x environments, higher [NO]/[NO 2 ] ratios lead to the formation of fewer products, whereas lower [NO]/[NO 2 ] ratios can induce the increase in SOA concentration. 109 For m -xylene, Li et al showed that SOA formation has strong correlations with [HO]/[HO 2 ], [HO 2 ]/[RO 2 ], and [NO]/[HO 2 ] in addition to [NO]/[NO 2 ].…”
Section: Factors Affecting Aromatic Soa Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Beyond this, photoinduced generation of reactive intermediate species without the use of an oxidant, typically performed in flow reactors or in jets under vacuum conditions, has allowed for more selective investigations of particular key reaction steps and the intermediates that lead to them. This includes the photolysis of alkyl iodides for R and RO 2 radicals, 69 of alkyl nitrites to form RO radicals, 70 and of diiodo compounds to form carbonyl oxides. 71 To date, most investigations of this type have been limited to small and/or unfunctionalized reactive intermediates, largely due to the fact that precursors to large, functionalized radicals are not commercially available.…”
Section: Challenges and Advances In Investigating The Chemistry Of Fu...mentioning
confidence: 99%